The cultural unspoken in Waciny’s «Lolita Fingers» - Zouak, Akila (Journal of Human Sciences, 2021)
This research paper seeks to identify some of the Cultural Systems embedded in one of the texts of the Algerian novelist "Wassini Al Araj". Such cultural Systems that have been created along with the production of literary texts have always remained hidden and consumed by the audience of readers without their awareness, or the awareness of the producer of the speech, which ensured its establishment and survival. Therefore, an additional interpretive effort is needed to help decipher them. The )thingnification( of women is probably one of the most serious of these Systems that has taken new ways by focusing on females and pushing them to practice sins in the name of freedom. This is what we will discover through this cultural critique, which delves into the hidden literary text, exploiting all the available precedent instruments.